Mechanical and thermal stability of eccentrically stiffened functionally graded conical shell panels resting on elastic foundations and in thermal environment. (15th November 2015) - Duc, Nguyen Dinh; Cong, Pham Hong; Anh, Vu Minh; Quang, Vu Dinh; Tran, Phuong; Tuan, Ngo Duc; Thinh, Nguyen Hoa
Abstract: Conical shell panels made of functionally graded materials (FGMs) are rather commonly used by structural engineers. However, due to their complex geometric shape, there are only a few studies on conical shell panels made from FGMs. This paper investigates the linear stability analysis of eccentrically stiffened FGM conical shell panels reinforced by mechanical and thermal loads on elastic foundations. The FGM conical shell is in thermal environment and both the panel and the stiffeners are deformed under temperature. The material properties of both the panels and stiffeners are assumed to be temperature-dependent. Classical shell theory and Lekhnitsky's smeared stiffeners technique are used to set the balance equations and linear stability. Shells are reinforced by stringers and rings. The effects of stiffeners, material, and mechanical and temperature loads on stability of the eccentrically stiffened FGM conical shell panels are analysed and discussed.